2009
DOI: 10.1115/1.3112386
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Turbulence Modeling Strategies for Indoor Flows

Abstract: Turbulence modeling techniques are compared for the simulation of low speed indoor air flow in a simple room. The effect of inlet turbulence intensity on the flow field is investigated using the constant coefficient large eddy simulation (LES) model with uniform mean inlet conditions at several levels of inlet turbulence intensities. The results show significant differences between the simulations with laminar inflow conditions and those in which turbulence was introduced at the inlet. For simulations with tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…Different turbulence models for building airflows were evaluated, including Reynolds‐averaged modeling (Chen, 1996; Murakami, 1998; Abdilghanie et al., 2009) and large eddy simulations (Mochida et al., 2005; Béghein et al., 2005). Owing to turbulence modeling difficulties, CFD may not be able to reveal the real physics as in experiments.…”
Section: Two Major Challenges In Cfdmentioning
confidence: 99%
“…Different turbulence models for building airflows were evaluated, including Reynolds‐averaged modeling (Chen, 1996; Murakami, 1998; Abdilghanie et al., 2009) and large eddy simulations (Mochida et al., 2005; Béghein et al., 2005). Owing to turbulence modeling difficulties, CFD may not be able to reveal the real physics as in experiments.…”
Section: Two Major Challenges In Cfdmentioning
confidence: 99%
“…[31] The general conservation equation contains a general variable, /, by which a balance between various processes within a finite control volume is made. The momentum, continuity, and turbulence equations can be derived from the following general equation: [11,32] …”
Section: A Transport Equationsmentioning
confidence: 99%
“…Joubert et al (1996) performed CFD simulations for the same case and for the same range of TI (between 4% and 37.4%) and also found no effect on the results. However, Abdilghanie et al (2009) assessed the influence of the inlet TI for a generic enclosure and found local differences of more than 100% for the mean velocities and the velocity fluctuations when comparing the results for inlet turbulence intensities of 5% and 13%. Cao and Meyers (2013) studied mixing ventilation flow in a cubical enclosure and found a clear effect of inlet turbulence conditions on the flow pattern calculated; detachment of the incoming wall jet was delayed with increasing TI (range between 5% and 30%).…”
Section: Physical Diffusionmentioning
confidence: 99%